Strategi Pengembangan Usahatani Sorgum pada Lahan Kering di Kabupaten Sumba Timur - Saragih, Elsa Christin; Wadu, Junaedin; Wadu, Ronaldo Bryan; Way, Priskila Anastasia Hunga (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
It is hoped that the development of a new production center for sorghum commodities, especially in East Sumba Regency, can increase sorghum production and supply sorghum needs nationally in order to face the world food crisis. To achieve this, it is important to be able to formulate the right strategy for developing sorghum in East Sumba Regency which has dry land conditions. The aim of this research is to analyze the internal and external environment of sorghum farming in East Sumba Regency and to determine priority strategies for developing sorghum farming in East Sumba Regency. This research is a qualitative research with analytical descriptive analysis conducted in July - December 2023 in East Sumba Regency. Respondents in this research were key informants who were determined using a purposive sampling technique. Data collection was carried out by means of field observations, Focus Group Discussions (FGD) and in-depth interviews according to research problems with key informants. The analytical methods used in this research are SWOT analysis and QSPM. The results of the SWOT matrix analysis show that there are 6 alternative strategy formulations that can be applied to the development of sorghum farming in East Sumba. Meanwhile, the results of the QSPM analysis show that the first priority alternative strategy that can be applied by farmers in developing sorghum farming on dry land in East Sumba is optimizing land use to increase production.